(3JaSjQ (B( (3bd CYhP HQH Gdadb(B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bhdg Ld LdGdg (B: ( (3bd CYhP HQH Gdadb (B) (3aGdb XdeI GdYOe HfhQ GdhLhO hgh GdeHOC GdChd GdhGLH GdhLhO dPGJg s
(3BNQgG (B:s
(3aeG GMSf aYdgG YfO GdEYQGV Yf Pdc heG GYXe dPGJgG GdeaGQbI Yfg Ef cGfJ jaGQbg HGdPGJ hGdYdGbI hdLejY GdMGdGJ QRbfG Gddg JYGdi GdJMQc GdJGe hGdebGd GdJGe HMb GdfHi eMeO hBdg GdWGgQjf Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B451s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJaSjQ hYdhe GdbQBfs